SBIR program diversity and assessment challenges : report of a symposium - Wessner, Charles W. (Online access: National Academy of Sciences National Academies Press., 2004)
As the Small Business Innovation Research (SBIR) program approached its twentieth year of operation, the U.S. Congress asked the National Research Council (NRC) to carry out a "comprehensive study of how the SBIR program has stimulated technological innovation and used small businesses to meet federal research and development needs" and make recommendations on improvements to the program. An initial conference to launch this assessment was convened in Washington, D.C. on 24 October 2002. It provided an opportunity for agency officials from each of the five departments and agencies accounting for 96 percent of SBIR program funds to provide an overview of their goals, operations, and challenges. It also included contributions from other agencies with SBIR programs. As the first comprehensive perspective on the SBIR program, the conference captured new information and understanding of its operation, challenges, and potential. It also reviewed the many measurement challenges involved in assessing the impact of this varied and complex program. Finally, the conference drew attention to the fact that while SBIR operations and accomplishments are sometimes discussed in general terms, the actual implementation of the program is carried out in agencies with quite distinct missions and interests.